(untitled) (Palíndromo, 2021)
The interview discusses the use of digital technology and digital media as paths for the arts, poetics and defense of the identities of native peoples. The interviewee is the artist Denilson Baniwa, an exponent of contemporary Brazilian art that uses different languages such as performance, drawings and laser projection. Its artistic production process also arises from the historical struggles of the indigenous movement in Brazil and surpasses this scenario with fictional proposals for the creation of other worlds through technology. In addition, the artist uses social networks as a channel of circulation and communication of greater reach to forge territories and identities. The interview was conducted during the covid-19 pandemic in a period of social isolation, which emphasizes the importance of access to art and digital technology in adverse times.